ENT 530 Social Media Portfolio: Lasagnalicious / Siti Nur Adilla Shaiful Bahrin - Shaiful Bahrin, Siti Nur Adilla (2020)
I chose this lasagna business because I am a hardcore lasagna fan. I really like eating beef lasagna. For me lasagna is an interesting Italian food with a combination of cheese + lasagna slices topping and their special sauce. It is very tasty to eat when hot because the cheese will be a little chewy. Lasagna is also one of the hard-to-find foods because not all places sell it. Most sell it only in cafes or western food restaurants. However, it is quite difficult to get the right lasagna according to my taste. For now, only lasagna at Secret Recipe, Tok ibu Kitchen and Rack Boutiques Cafe are my favorites. The difficulty of getting this lasagna stock has given me an idea to sell lasagna to make it easier for lasagna lovers to get their favorite food. I did a study on lasagna recipes on the internet to make sure the lasagna I produced would be comparable to lasagna at the Italian food cafe out there. In the beginning, I gave a try to my relatives and close friends to value the taste of the lasagna I produced. I accept the criticism they give to improve the taste of my lasagna because I want when I sell lasagna later will give satisfaction to my customers. After getting satisfaction and improving my lasagna, now is the result of my small business, Lasagnalicious